Investigation of transport properties in polymer/fullerene blends using time-of-flight photocurrent measurements - Choulis, Stelios A.; Nelson, Jenny K.; Kim, Yong Rok (My University, 2003)
The electron and hole transport properties of blends of poly[2-methoxy-5-(3′,7′-dimethyloctyloxy)-1-4-phenylene vinylene], (MDMO-PPV) and [6,6]-phenyl C61-butyric acid methyl ester (PCBM) are investigated at room temperature using time-of-flight photocurrent measurements as a function of blend composition and laser excitation intensity. The experimental results are consistent with the notion of a mobility edge for holes in this material that delineates long-lived trapping and mobile carrier states. Electron transport in PCBM appears to be less dispersive than that of holes in MDMO-PPV in the blend, with electron mobilities in the former exceeding hole mobilities in the latter by up to two orders of magnitude. Photocurrent generation in corresponding solar cell devices may therefore be limited by the low hole mobility of MDMO-PPV
Keywords: Blends; Polymers; Fullerenes; Electron mobility; Esters; Solar cells